An inter-provincial cooperation model under Renewable Portfolio Standard policy. (15th April 2023) - Zeng, Lijun; Du, Wenjing; Zhang, Wencheng; Zhao, Laijun; Wang, Zhaohua
Abstract: The Renewable Portfolio Standard (RPS) has been implemented by a number of the world's most economically developed nations, to address the great challenges faced regarding energy problems and climate change. However, the current non-cooperation model (NCM) of the RPS in China cannot effectively overcome the bottleneck of renewable energy development due to the disparity between renewable energy-rich regions and high energy-consuming regions. To resolve this dilemma, this study proposes an inter-provincial cooperation model (ICM) under the RPS in China. The ICM consists of two parts: (1) an optimization model to obtain the lowest RPS target realization cost and ensure efficiency, and (2) cost allocation models based on the Shapley value, core, and nucleolus methods, to ensure fairness in different situations. The cases of Beijing, Shandong, Shanxi, and Inner Mongolia show that the total cost of the four provincial regions covered by the ICM will be reduced by 57.07 × 10 8 CNY, or 8.25% compared with the NCM. Sensitivity analysis was conducted to test the impact of different parameter values on the ICM results. Based on these results, we propose policy recommendations to promote implementation of the ICM. Highlights: An inter-provincial cooperation model (ICM) under RPS is constructed and validated. The ICM can overcome the bottleneck of renewable energy development effectively. The ICM ensures the efficiency and fairness in different situations. The ICM can reduce the cost of each participating province significantly.